2002
DOI: 10.3390/i3070790
|View full text |Cite
|
Sign up to set email alerts
|

A Protons Exchanged Montmorillonite Clay as an Efficient Catalyst for the Reaction of Isobutylene Polymerization

Abstract: The polymerization was performed under suitable conditions at isobutylene vaporization temperature (-7°C). Experiments revealed that polymerization induced by "H-Maghnite" proceed in bulk and in solution. In contrast to findings with methylene chloride CH 2 Cl 2 as a polar solvent, polymerization yields with hexane C 6 H 14 non-polar solvent is very significant.In bulk polymerization, Isobutylene conversion increases with increasing "H-Maghnite" proportion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 10 publications
5
31
0
Order By: Relevance
“…The composition and the structure of Maghnite-H + were reported in a previous works 10,18 , in which we have demonstrated that 10 , the other peaks are related to the structure of Montmorillonite aluminum-oxygen octahedron and silicon-oxygen tetrahedron 10,20 . The comparison between the diffractograms of Maghnite ( figure 2(a) ) and Maghnite/Polymer mixture after the reaction ( figure 2 (b) ), shows that there are no significant changes on the cristallogaphic structure of Maghnite-H + after the reaction.…”
Section: Maghnite Structuresupporting
confidence: 76%
See 3 more Smart Citations
“…The composition and the structure of Maghnite-H + were reported in a previous works 10,18 , in which we have demonstrated that 10 , the other peaks are related to the structure of Montmorillonite aluminum-oxygen octahedron and silicon-oxygen tetrahedron 10,20 . The comparison between the diffractograms of Maghnite ( figure 2(a) ) and Maghnite/Polymer mixture after the reaction ( figure 2 (b) ), shows that there are no significant changes on the cristallogaphic structure of Maghnite-H + after the reaction.…”
Section: Maghnite Structuresupporting
confidence: 76%
“…The spectra provide information about the local environment of the aluminum sites in Maghnite, two small bands of two tetra-coordinated AlO 4 (Al TD1 and AL Td2 ) at 58-60 ppm and 68-71 ppm, and another signal at 3-4 ppm attributed to octahedral AlO 6 (Al Oh ) 25 . AlO 4 sites in the maghnite structure are the consequence of isomorphic ions substitution within the silicate layers 10,[15][16][17] . Meanwhile, the 27 Al NMR spectra of Maghnite-H + and of Maghnite-H + /Polymer mixture after the reaction were closely identical, two very significant differences were observed in the 27 Al NMR spectra.…”
Section: 4mentioning
confidence: 99%
See 2 more Smart Citations
“…Montmorillonites, a class of inexpensive and noncorrosive solid acids, have been used as efficient catalysts for a variety of organic reactions. The reactions catalyzed by montmorillonites are usually carried out under mild conditions with high yields and high selectivities, and the workup of these reactions is very simple; only filtration to remove the catalyst and evaporation of the solvent are required, maghnite-H + can be easily recovered and reused, after it has separated from the polymer, it was rinsed with water and dried by heating to a temperature above 100 °C and finally crushed [19,20]. To ensure good performance, the Maghnite-H + can be reactivated with acid [21,22].…”
Section: Introductionmentioning
confidence: 99%